Electrocardiographic evidence of ischemia in a young male with anomalous origin of a coronary artery from the opposite sinus. (December 2019) - Rogers, Timothy P.; Samyn, Margaret; Gudausky, Todd M.
Abstract: Congenital coronary artery anomalies are a well-known cause of life-threatening syncope, but usually present with either cardiac arrest, or after resolution of the episode. We discuss a young man with exertional syncope, who upon evaluation in the field, had electrocardiographic evidence of severe but transient myocardial ischemia. This case provides rare insight into the pathophysiology of sudden cardiac death in patients with anomalous left coronary artery from the right aortic sinus. Highlights: Anomalous coronary arteries that travel between the aortic root and pulmonary trunk with an intramural course have been consistently shown to be associated with SCD We present a case of a young man with such an abnormality who experienced a syncopal event due to myocardial ischemia. This ischemia and its subequent resolution was documented by emergency medical service personnel via electrocardiogram testing.